Proactive Measures to Combat a SARS-CoV-2 Transmission Among High Risk Patients and Health Care Workers in an Outpatient Dialysis Facility - Pillai, Jayandiran; Motloba, Pagollang; Motaung, Keolebogile Shirley Caroline; Wallis, Carole; Ozougwu, Lovelyn Uzoma; Basu, Debashis (Frontiers in Pharmacology, 2021)
Background: End-stage-renal-failure (ESRF) patients attending clustered out-patient dialysis are susceptible to SARS-CoV-2 infection. Comorbidities render them vulnerable to severe COVID-19. Although preventative and mitigation strategies are recommended, the effect of these are unknown. A period of ‘potential-high-infectivity’ results if a health- care-worker (HCWs) or patient becomes infected. We describe additional proactive measures and a clinical pathway to mitigate an outbreak, once a positive individual has been identified. Aim: Methodology: We describe the management of 57 patients and 11 HCWs in an outpatient hemodialysis-unit, after one of the patients tested positive for SARS-CoV-2. All individuals were subjected to RT-PCR tests and biomarkers (Neutrophil-Lymphocyte-Ratio, C-reactive-protein, and D-Dimer) within 72-hours (initial-tests). From these, we identified other positive individuals and a RT-PCR negative subgroup with abnormal biomarkers (suggestive of significant comorbidities or probable false negative RT-PCR). The latter subgroup underwent clustered dialysis and during the second week, were retested (RT-PCR and biomarkers). Results: A second positive-patient was identified. In the positive-patients, biomarker improvement coincided with RT-PCR negative tests. We identified 13 individuals for retesting. None of the retested individuals tested positive and there was no deterioration in median biomarker values between initial and retest. Conclusion: Immediate RT-PCR testing of patients and HCWs together with selective retesting, based on abnormal biomarkers seems plausible. Chronic symptoms are common in ESRF patients. Observing dynamic changes in biomarkers in RT-PCR positive and negative-patients may provide insights into general state of health. Selective RT-PCR retesting in a group vulnerable for COVID-19, is a novel strategy that requires further investigation.